Reimagining Search. - Wright, Alex (Communications of the ACM, 2016)
The article discusses search engine optimization with a focus on returning queries rather than text strings. The integration of machine learning into search engines is described, the development of search engine algorithms and models by computer scientist Daniel Tunkelang is examined, and information is offered on the use of voice recognition software and structured data in internet searches of technology company Google.